The Sources of Economic Energy. - Greco Nino (European Regional Science Association (ERSA), 2006)
The time and space so loved by philosophers and poets, burden and delight of physicists and astronomists, for a long time have been more for economists elements of inconvenience than of analysis. All this finds a justification in the mechanistic logic which also regulates the great economic theories. But the "Newtonian" general economic theory, fascinating though it is and irreplaceable in conferring rigour to theoretical formulations and reducing to a simplified form the apparently (or real) chaos of the great systems, in its necessarily high flying it is unsuitable to interpreting the local level where, instead, it is indispensable to keep one's feet on the ground, to move in the territory following the infinite combinations of the surrounding countryside, to worm oneself into the maze of economic and social interrelations which make it unique and unrepeatable.The long journey began with the Solow type neoclassical growth models, characterised by the production function with decreasing returns and with perfect market forms, passing through endogenous growth models, now reaches territorialised forms, which have the advantage of being less abstract than neoclassical models, in that they operate in imperfect markets, but which do not manage to keep the growth rate under control, which is always given as positive. From "implosive" models we pass to "explosive" models.Forceably including local interrelations into classical production functions is not successful in overcoming the basic contradictions between Newtonian determinism and localistic indeterminism, with the result that the classical elegance is lost without acquiring localistic concreteness Now the new physicists are trying again with the String Theory, above all in the M version or the Theory of Everything. But this fascinating theory does not yet allow us to understand some fundamental things, for example it does not tell us why particles align in a certain way, in a certain order and with a certain potential. Adapting concepts and paths elaborated by post-Newtonian physics, the economist could do much less and a bit more. Much less because he is not required to solve in any way the mysteries of the universe, a bit more because, perhaps, he can describe without contradictions, using known economic science, what physicists, in their field, are not able to describe: he can tell us, using formal models why at a certain point in time and space a determined productive set composed of a well defined number of "economics quanta" relative to material and immaterial elements, of which is known the magnitude, order and force, behaves like a string and begins to "vibrate" setting off the chain reaction of economic development.
Keywords: 330